Simulated Twentieth‐Century Ocean Warming in the Amundsen Sea, West Antarctica - Naughten, Kaitlin A.; Holland, Paul R.; Dutrieux, Pierre; Kimura, Satoshi; Bett, David T.; Jenkins, Adrian (Geophysical Research Letters, 2022)
Rapid ice loss is occurring in the Amundsen Sea sector of the West Antarctic Ice Sheet. This ice loss is assumed to be a long‐term response to oceanographic forcing, but ocean conditions in the Amundsen Sea are unknown prior to 1994. Here we present a modeling study of Amundsen Sea conditions from 1920 to 2013, using an ensemble of ice‐ocean simulations forced by climate model experiments. We find that during the early twentieth century, the Amundsen Sea likely experienced more sustained cool periods than at present. Warm periods become more dominant over the simulations (mean trend 0.33°C/century) causing an increase in ice shelf melting. The warming is likely driven by an eastward wind trend over the continental shelf break that is partly anthropogenically forced. Our simulations suggest that the Amundsen Sea responded to historical greenhouse gas forcing, and that future changes in emissions are also likely to affect the region.